PENGEMBANGAN INSTRUMEN ASESMEN KINERJA DASAR TATA RIAS - Sudirtha, I Gede (Universitas Pendidikan Ganesha, 2014)
This study aims to develop a performance assessment instrument for Make up Training Subject in Beauty Education Program by appropriate validity and reliability procedure in thedevelopment of the assessment instrument as the assessment process and products. Thisresearch is a development research (R&D). The research focuses on the development ofassessment instrument for Makeup Training Subject. The aspects of research, data sources, techniques and instruments/data collection instrument, and validation and reliability of theinstrument used in the study conducted by interview, observation, and literature and documents.The data of this study is quantitative data, which was statistically analyzed due to relevant empirical testing (validation of instruments) that includes testing and content validity andinternal validity. Descriptive analyzes were undertaken to describe the research data. The results showed: 1) The design of the instrument Makeup Training Subject are developed through theneeds analysis. It is done through literature review and study of the course competencies byengaging a team of researchers. This study resulted in the instrument guidelines and assessment instrument completed with its scoring rubrics. The instrument comprising: a step of validityassessment is done through the stages: experts judgment, empirical tests to prove the validityand reliability of the instruments assessment. All the performance test instrument developed is